Analisis Faktor yang Mempengaruhi Prilaku Seks Pra Nikah pada Remaja Menggunakan Teori Planned Behavior (TBP) - Ghalin Annisa Widiya (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2026)
Premarital sexual behavior among adolescents is a reproductive health issue that continues to increase and has become a serious concern in many countries, including Indonesia. This phenomenon is influenced by various interrelated psychological, social, cultural, and environmental factors that affect adolescents’ physical and mental well-being. This study aims to analyze the factors influencing premarital sexual behavior among adolescents using the Theory of Planned Behavior (TPB) approach, which consists of three main components: attitude, subjective norms, and perceived behavioral control. The research method employed is a literature review, examining relevant and indexed national and international journals to obtain a comprehensive overview of the determinants of premarital sexual behavior among adolescents. The findings indicate that all three TPB components significantly contribute to adolescents’ intentions to engage in premarital sexual behavior. Among these factors, subjective norms such as the influence of peers, family, and the social environment emerge as the most dominant in shaping adolescents’ intentions and decisions. These results highlight the importance of family-based interventions, comprehensive and continuous sexual education, and the strengthening of self-control and decision-making abilities among adolescents. Therefore, this study is expected to serve as a foundation for designing more effective, contextual, and behavior-oriented programs for the promotion and prevention of adolescent reproductive health.